A Comprehensive Review on Nutraceuticals and Its Impact on Healthcare - Ismail. Y; Yuvarani T; Voleti Vijaya Kumar (Pharmaceutical Science: New Insights and Developments Vol. 4, 2025)
Nutraceuticals are bioactive products that merge the benefits of nutrition and medicine to enhance health and prevent chronic diseases. They play a crucial role in managing conditions associated with oxidative stress, including cardiovascular diseases, diabetes, inflammation, ophthalmic disorders, and immune-related illnesses. Often considered a bridge between food and medicine, nutraceuticals encompass herbal remedies, natural foods, specific nutrients, vitamins, dietary supplements, and functional foods such as soups, juices, cereals, and beverages. Nutraceuticals are broadly categorized into conventional and unconventional types. Conventional nutraceuticals, such as omega-3 fatty acids and dietary fiber, have well-established health benefits. In contrast, unconventional nutraceuticals are still under investigation for their potential therapeutic effects. While nutraceuticals offer numerous advantages, including improved overall health and reduced risk of chronic illnesses, they also pose potential risks, such as drug interactions, adverse side effects, and the possibility of overdose. As interest in nutraceuticals continues to grow, ongoing research is essential to fully understand their efficacy, safety, and role in modern healthcare.